Topics in analytical political economy - Hinich, Melvin J.; Barnett, William A. (Elsevier, 2007)
The nine papers in this volume are a diverse set of quality contributions to the field in economics that is called political economy. It is important to understand that social scientists hold different interpretations of the term political economy. Most mainstream economists expect a paper in the field to use the same models as are used in neoclassical economics, be it micro or macro. The field of political economy is seen by most economists to be exclusively the purview of their field. However, the political system of a country determines the nature of its economics system. The economy feeds back to the political system but the rules of the game are determined by the political system.The study of politics is the hardest task in the social sciences. The political system defines the scope of the economics system while taking resources from the economy in order to run campaigns and produce the types of compromises that are required of a stable political system that allows economic agents to make sensible investments. The interaction between the highly inter-dependant yet very different fields of politics and economics forms the basis of this volume. It contains a collection of key papers on the topic of analytical political economy. The papers authored by some of the foremost experts in the field. It is part of the ISETE series.
Keywords: Economics -- Congresses.; Political science -- Congresses.; Economic policy -- Congresses.; elektronické knihy; electronic books